The Influence Of Perceived Risk On Digital Banking To Customer's Intention To Use Digital Banks In Jabodetabek 2023-2024 - Louis, Evannia Immanuel; Kurnia Fajar Afgani (Integrasi Sains Media, 2024)
Digital banks are banks that have limited to no physical offices and are accessed through an online application. In the past seven years, digital banking has become a leading digital payment method, used by approximately 78% of Indonesians as of 2021. Although digital banking has gained popularity, there is a significant disparity between Indonesian customer’s willingness to use and actual use of digital banks. The reason for the disparity is perceived risks, which proved to be a resistance factor to customer intention through previous research of Technology Adoption Model (TAM) of digital banks. This research aims to analyze how the perceived risk of digital banks influences customer’s intention to use digital banks, which perceived risk factor has the highest influence on intention to use, and identify the correlation between perceived risk factors towards intention to use. By drawing from perceived risk theories across decades, six risk dimensions – financial, performance, social, time, security, and privacy risk – were analyzed. This research collected 400 Jabodetabek respondents through an online questionnaire, which were analyzed with descriptive statistics and Structural Equation Modeling (SEM). The hypothesis testing was done using the bootstrapping method with a two-tailed t-test with 5% significance level, while the correlation was calculated with SEM. The results reveal that the overall level of perceived risk in Jabodetabek is relatively low with only one out of six risk factors proving to be significant. It was found that security risk is the only risk factor that significantly influences customer intention to use digital banks, with a negative correlation of 30.3%. In light of this finding, this research provides practical recommendations for digital bank managers to minimize security risk and for future study. This research hopes to help digital bank managers in enhancing customer intention to use digital banks by reducing perceived risk factors.